Perkawinan Adat Merari’ Suku Sasak dalam Perspektif Hukum Adat : Studi Kasus di Desa Kateng Kecamatan Praya Barat Lombok Tengah - Amalia Solikha; Ismi Lailatul Maulida; Rahayu Sri Utami (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Marriage is a universal social institution, yet its implementation is profoundly shaped by distinctive local cultural values. One such cultural manifestation is the Merari’ tradition practiced by the indigenous Sasak community in Central Lombok, West Nusa Tenggara. This tradition refers to the practice of